Asymmetric Organocatalytic Synthesis of trans-3,4-Disubstituted Isochromanones via an Intramolecular Aldol Reaction - Fronert, Jeanne; Bisschops, Tom; Cassens-Sasse, Elisa; Atodiresei, Iuliana; Enders, Dieter (Synthesis, 2013)
The diastereo- and enantioselective synthesis of 3-acetyl-4-hydroxyisochroman-1-ones via an intramolecular trans-selective aldol reaction employing proline-type organocatalysts is described. Good yields (64–88%) and high stereoselectivities (87 to >95% de, 84–99% ee) are obtained, thus potentially enabling, for example, a new direct entry to carbazolelactone alkaloid natural products.
Keywords: organocatalysis; aldol reaction; asymmetric synthesis; dihydroisocoumarin; enamine activation